2010
DOI: 10.1017/s1368980010002004
|View full text |Cite
|
Sign up to set email alerts
|

Meat consumption and risk of type 2 diabetes: the Multiethnic Cohort

Abstract: Objective: To examine the association of meat consumption with diabetes risk in the Hawaii component of the Multiethnic Cohort and to assess effect modification by ethnicity. Design: A prospective cohort study. Baseline information on diet and lifestyle was assessed by questionnaire. The cohort was followed up for incident cases of diabetes, which were identified through self-reports, medication questionnaires, or health plan linkages. Cox regression was used to calculate hazard ratios (HR) and 95 % confidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 18 publications
4
54
2
Order By: Relevance
“…These findings are consistent with several other prospective studies in whites and health professionals that showed a positive association of processed meats and incident diabetes (1)(2)(3)(4)(26)(27)(28)(29) and no association of unprocessed red meats and incident diabetes (1,2,4). In contrast, a large meta-analysis suggested that both processed meat and unprocessed red meat are associated with higher risk of diabetes; however, the association of processed meat and incident diabetes was considerably stronger than for unprocessed red meat (27).…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with several other prospective studies in whites and health professionals that showed a positive association of processed meats and incident diabetes (1)(2)(3)(4)(26)(27)(28)(29) and no association of unprocessed red meats and incident diabetes (1,2,4). In contrast, a large meta-analysis suggested that both processed meat and unprocessed red meat are associated with higher risk of diabetes; however, the association of processed meat and incident diabetes was considerably stronger than for unprocessed red meat (27).…”
Section: Discussionsupporting
confidence: 91%
“…112 Likewise, a positive correlation was observed between red and processed meat intake and risk of diabetes mellitus in a multiethnic study of 29 759 white, 35 244 Japanese-American, and 10 509 Native Hawaiian men and women in Hawaii, aged 45 to 75 years. 113 Similar observations were made in the Swedish women cohort of 43 396 by Lagiou et al (2012). They reported a 5% increase in incidences of CVD with a 5 g increase in protein intake or 20 g reduction in carbohydrate intake.…”
Section: Human Clinical Trials Epidemiological Studies Diet and Cvdsupporting
confidence: 63%
“…This positive association seems, however, to be driven by different types of meat consumed among women and men (red and processed meat for men, red meat and poultry for women). The finding of a positive association between type 2 diabetes and poultry consumption in women is not consistent with findings in several previous studies [24][25][26]. In their meta-analysis, Pan et al [6] modelled the substitution of total red meat consumption with poultry consumption and showed a lower risk of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 58%